HUBUNGAN ANTARA SELF ESTEEM DAN SUBJECTVE WELL BEING PADA REMAJA MADRASAH ALIYAH YANG TINGGAL DI PONDOK PESANTREN Al-ISLAM KAB.GORONTALO - Siskawati Siskawati; Rahmawaty Parman; Anik Indarwati (program studi psikologi, 2024)
This research aims to determine the relationship between self-esteem and subjective well-being in madrasah Aliyah teenagers who live in the Al-Islami Islamic boarding school in Gorontalo district. This research is a form of quantitative research with a sampling technique using simple random sampling technique and the sample in this research was 60 students. Data were collected using a self-esteem scale and a subjective well-being scale and analyzed using the pearson product moment correlation the results of the research show that there is a relationship between self- esteem and subjective well-being in students with a correlation coefficient value of 0.698 with a significant relationship between self-esteem and subjective well-being among madrasah Aliyah teenagers who live in the Al-Islam Islamic boarding school Gorontalo Regency.